Environmental Sustainability: Key to Achieving Other Millennium Development Goals (MDGs). - Yusuf, Babatunde Rahman; Idowu, Khadijah A.; Adebayo, Mudashiru A.; Yaqub, Jemilah (IJRDO - Journal of Business Management, 2015)
Millennium Development Goals are grounded in the recognition of the role played by the environment and natural resources in providing the material and environmental basis, the ecosystems, and the energy on which economic processes depend. This study sets out to establish an association model between environmental sustainability (MDG 7) and the achievement of the Millennium Development Goals. This study stems from the fact that environmental sustainability is the key to the achievement of all the MDGs which focuses on the environmental impacts of urban agglomerations, as it aims to improve the lives of 100 million urban slum dwellersby 2015. The study adopted a descriptive research design and was guided by seven research questions. 637 respondents were randomly sampled and analyzed using regression. The results show that there is a relationship between Environmental Sustainability (ES) and the achievement of the Millennium Development Goals. The study recommends that population growth should be linked to environmental sustainability for the achievement of Millennium Development Goals (MDGs).